Challenging Methicillin Resistance Detection in Bone and Joint Infections: Focus on the MRSA/SA SSTI® Strategy - Titécat, Marie; Loïez, Caroline; Demaeght, François; Leclerc, Jean-Thomas; Martin, Théo; Dezèque, Hervé; Migaud, Henri; Senneville, Eric (Frontiers in Medicine, 2021)
The genus Staphylococcus is the main causative agent of bone and joint infections (BJI) which outcomes are impacted by both effective surgical and appropriate antimicrobial management. In this context, methicillin resistance (MR) detection is a microbiological challenge to optimize the anti-staphylococcal drug coverage and to secure the surgical procedure. During the last decade, molecular tools have been developed to detect rapidly bacterial resistant strains in clinical samples. The GeneXpert MRSA/SA SSTI® assay (Cepheid, Sunnyvale, CA, USA) is a real-time PCR method aimed at detecting methicillin-resistant Staphylococcus aureus (MRSA) in skin and soft tissues infections. In the literature, this test has been reported to be diverted from its original purpose to be evaluated in surgical samples. Within the current review, we update the GeneXpert MRSA/SA SSTI® assay performance in staphylococcal species determination (i.e. S. aureus versus coagulase negative species) together with MR genotype detection, when performed in osteoarticular infections.